Secure Encrypted Steganography Graphical Password scheme for Near Field Communication smartphone access control system - Cheong, S.; Ling, Huo Chong; Teh, P. (Pergamon, 2014)
The revolutionary development of smartphone which offers compelling computing and storage capabilities has radically changed the digital lifestyles of users. The integration of Near Field Communication (NFC) into smartphone has further opened up opportunities for new applications and business models such as in industry for payment, electronic ticketing and access control systems. NFC and graphical password scheme are two imperative technologies that can be used to achieve secure and convenient access control system. One of the potential uses of such technologies is the integration of steganography graphical password scheme into NFC-enabled smartphone to transcend conventional digital key/tokens access control systems into a more secure and convenient environment. Smartphone users would have more freedom in customizing the security level and how they interact with the access control system. As such, this paper presents a secure two-factor authentication NFC smartphone access control system using digital key and the proposed Encrypted Steganography Graphical Password (ESGP). This paper also validates the user perception and behavioral intention to use NFC ESGP smartphone access control system through an experiment and user evaluation survey. Results indicated that users weigh security as a dominant attribute for their behavioral intention to use NFC ESGP smartphone access control system. Our findings offer a new insight for security scholars, mobile device service providers and expert systems to leverage on the two-factor authentication with the use of NFC-enabled smartphone. © 2013 Elsevier B.V. All rights reserved.